Revision of the peristediid genus Satyrichthys (Actinopterygii: Teleostei) with the description of a new species, S. milleri sp. nov. - Kawai, Toshio (Zootaxa, 2013)
The Indo-Pacific peristediid genus Satyrichthys Kaup, 1873 was first diagnosed as having a broad head with mesethmoid, postocular, parietal and preopercular spines. Later, most ichthyologists characterized Satyrichthys by its toothless jaws and strong preopercular spine. Kawai (2008) divided Satyrichthys into two genera, Satyrichthys and Scalicus, on the basis of a phylogenetic hypothesis, and redefined Satyrichthys. Seven species of Satyrichthys are recognized here, including one new species: S. clavilapis, S. laticeps, S. longiceps, S. milleri sp. nov., S. moluccensis, S. rieffeli and S. welchi. The new species is distinguished from its congeners in having equilateral-triangular rostral projections, 4 lip and 4 chin barbels, and no anterior directed spines on the upper lateral row of the caudal peduncle. Satyrichthys laticeps, previously treated as a junior synonym of S. moluccensis, is regarded as a valid species. The following new synonyms are noted: S. adeni, S. halyi and S. magnus are all junior synonyms of S. laticeps; S. isokawae is a junior synonym of S. moluccensis; and S. lingi is a junior synonym of S. welchi. In addition, a neotype is designated for S. moluccensis.